Water crisis as an investment opportunity - Borovec, Adam; Brůna, Karel, 1973-; Tesařová, Žaneta; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
Bachelor thesis’s main topic of examination is the process of investing in water, which aims to mainly make a profit for the investor, but also to improve infrastructure of its supply system, the technology to utilize water and water related services. The main goal of this thesis is to analyse and evaluate the profitability of water for investors. The added value of this thesis lies in the potential of further development of investing in water and pointing out its current situation.
Vedoucí práce: Karel Brůna
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses